(3eMGVQGJ aj GdGbJUGO GdHJQhdj (B/s - (3GdOhQj, eMeO CMeOs ((3GdLRGFQ (B:s (3OjhGf GdeWHhYGJ GdLGeYjI GdLRGFQ ,s, 1983)
(3JYQja HGdGbJUGO hGdUfGYI GdHJQhdjI(B, (3GdJQcR GdGMJcGQj aj GdUfGYI GdHJQhdjI(B, (3GdWdH GdHJQhdj(B, (3GdSYQGdHJQhdjs
Keywords: (3GdEbJUGOs; (3GdHJQhds; (3GdUfGYIs